Investigation of the radial bearing force developed during actual ship operations. Part 1: Straight ahead sailing and turning maneuvers. (15th January 2015) - Ortolani, Fabrizio; Mauro, Salvatore; Dubbioso, Giulio
Abstract: The quantification of the radial force exerted by the propeller is of paramount importance for the improvement of the design procedures as well as for enhancing the prediction of the controllability and maneuvering qualities of oceangoing vessels. In this work the radial load experienced by the bearing strut of a twin screw configuration is experimentally investigated by free running model tests carried out at the CNR-INSEAN outdoor maneuvering basin. To this purpose the model has been equipped with a novel, in-house developed, two-component transducer. Results obtained for the straight ahead motion for a large range of speeds ( 0.05 < F N < 0.425 ) and turning circle maneuvers at different rudder angles (15°–35°) and three different speeds ( F N =0.218, 0.32 and 0.35) are presented and discussed in this paper. The main task is also to identify, from a phenomenological perspective, the nature of this load, in particular during tight maneuvers, characterized by critical overloading of the propellers. The use of the free running, self-propelled model, is the best way to gain a deeper insight on the loads generated by the propeller during quasi-steady and, especially, transient motions that are difficult to reproduce in a towing tank via captive model tests. Abstract : Highlights: Quantification of the bearing radial force. Development and application of a novel 2-component transducer. Analysis in straight ahead condition and turning circles by means of free running model tests. Phenomenological description of the generation of these loads. Approximate procedure to derive the propeller lateral force.